Conflict or cooperation? How does precipitation change affect transboundary hydropolitics? - Qifan Xia (IWA Publishing, 2021)
Global climate change affects hydrology and ecology, and aggravates the contradiction between water resources supply and demand, thus leading to transboundary water conflict and cooperation attracting increasing attention. This paper uses the precipitation data sourced from the Global Precipitation Climatology Centre, hydropolitical data collected from the Transboundary Freshwater Disputes Database and, for approximately half a century of socioeconomic indicator for countries, to discuss the relationship between precipitation change and transboundary hydropolitics. As demonstrated by the panel regression results, lower precipitation would lead to more water conflicts and more significant change of precipitation would lead to more water hydropolitical events. This result remains robust after adjustment being made to the defined thresholds of conflict and cooperation. The findings suggest that the countries in a transboundary river ought to avoid conflict and seek more cooperation, considering the uncertain prospect of precipitation changes. HIGHLIGHTS Changes in precipitation have been blamed for the increase in transboundary hydropolitics.; We reviewed the literature on the relationship between precipitation changes and hydropolitics and proposed a hypothesis on the relationship of precipitation change and hydropolitics.; Visualizing the distribution of water conflict and water cooperation, we seek to the relationship between precipitation change and hydropolitics.;